2020
DOI: 10.1136/bmjoq-2020-001022
|View full text |Cite
|
Sign up to set email alerts
|

How to rapidly design and operationalise PPE donning and doffing areas for a COVID-19 care facility: quality improvement initiative

Abstract: IntroductionEffective implementation of standard precautions specific to COVID-19 is a challenge for hospitals within the existing constraints of time and resources.AimTo rapidly design and operationalise personal protective equipment (PPE) donning and doffing areas required for a COVID-19 care facility.MethodsLiterature review was done to identify all issues pertaining to donning and doffing in terms of Donabedian’s structure, process and outcome. Training on donning and doffing was given to hospital staff. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Both routes of transmission, HCW to patients and HCW to HCW, were successfully addressed in infection control training sessions in which HCW were instructed in the correct handling of personal protective equipment and in social distancing measures. Several reports point out the importance of verbal training sessions demonstrating that HCW education does not only improve the handling of PPE but also reduces anxiety and increases the sense of preparedness [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both routes of transmission, HCW to patients and HCW to HCW, were successfully addressed in infection control training sessions in which HCW were instructed in the correct handling of personal protective equipment and in social distancing measures. Several reports point out the importance of verbal training sessions demonstrating that HCW education does not only improve the handling of PPE but also reduces anxiety and increases the sense of preparedness [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is critical given previous published data highlighting self-perceived proficiency is a poor predictor of proper PPE use 24 and use of dofficers providing verbal directions in COVID-19 settings is important to help support safety and quality of care. 10,25 Previous research has found that a bundled approach to addressing COVID-19 transmission on a respiratory medicine unit at a Singaporean hospital can be successful. 3 The study implemented a bundle including infrastructure enhancements, PPE audits, social distancing requirements, masking of patients when not eating, and enhanced environmental cleaning protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although the donning phase is associated with a low risk of contamination, doffing is a critical phase and greatly increases the risk of contamination of caregivers [5][6][7][8][9]. One of the strategies that effectively contributes to reducing staff self-contamination is doffing in structured areas dedicated to the removal of PPE [10,11]. However, this strategy is difficult to apply in the prehospital field, where health care workers must often doff PPE on site.…”
Section: Background and Importancementioning
confidence: 99%